Zrównoważony rozwój gospodarczy - moda czy utrwalony trend? - Klepacki, Bogdan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
In the paper Author has presented the main conditions to promote the concept of world's sustainable development. He states that this theory has good outlook to become the leading one in the coining decades. This results from the fact that the acceptability of the sustainable development is motivated by the imperative of survival and extending benefits, the imperative of acting and the imperative of imitation. The close link between the economic, ecological and social aspects both with ethical values which must determine this interdependent triangle framework cause that the concept of sustainable development has chance to extend from economic theory to socio-philosophical theory.